COMMUNICATION MANAGEMENT AMONG ATHLETE AND COACHES - Ezzeldin R. Aly (European Scientific Journal, ESJ, 2014)
This study examines how managers and coaches manage communication with athletes in team and individual sports. Communication is a process that requires a wide range of skills. We develop verbal and non-verbal communication in various ways. Communication is a critical element in the relationship between coaches and athletes in team and individual sports, and also between managers, referees, scorers, and other officials, yet there is little extant research in sport management that involves direct measures of Development Communication Management (DCM). In this study the researcher is looking for the process of communication which makes message interpretation more reliable. The researcher surveyed over 200 athletes and 14 head coaches in the Wisconsin Intercollegiate Athletic Conference (WIAC) to find some foundations for DCM. To aid the development of communication management with team sports, individual sports, coaches, referees, scorers, and others to enhance the management performance of communication. We looked at ways in this study to increase and make progress in the DCM. The researcher found ways to improve the management of communication before, during and after the sport events. DCM needs to be organized inside the team, so the coaches and managers can communicate effectively with athletes, colleagues, referees, scorers and other officials. Data was collected using two questionnaires designed by the researcher – one for coaches and one for athletes -- that employed a 5.0 Likert scale. The researcher used MANOVA models to test for significant differences between coaches and athletes, between genders, team, and individual sports. The significance level was set at p^.05. This study found a significant difference between male and female athletes in terms of their use of special gestures or signs during games or competition. On average males were neutral to slightly in agreement regarding the use of special gestures or signs while females were in slight disagreement. With the results related to communication styles, on average female athletes indicated that visual communication is their fastest mode of communication. On the other hand, they indicate that they were in slight disagreement regarding the use of special gestures or signs. This apparent inconsistency was a potential opportunity for DCM. A natural recommendation is to increase the use of special signs and gestures for female athletes. The results from the present study indicate that there are marked differences in communication practices of coaches and athletes and between team and individual sports. The results suggest that to aid in the development of communication management within team sports, coaches and athletes should determine what the fastest mode of communication is. Rather than watching for a visual sign, an athlete may instead be listening for a verbal cue if their coach finds verbal communication to be faster than visual. In this way, the coaches and athletes can progress in DCM. Knowing the best time to communicate will lead to DCM as a coach or manager uses DCM whenever it is necessary and beneficial for the athletes to encourage and motivate the athlete to do their best during their event. There is a significant difference between team and individual athletes in terms of who they communicate with most frequently (p-value < .001). Athletes of team sports agreed that they communicate most with their coaches while athletes of individual sports agreed that they communicate most with their teammates (Turman, Paul; D 2008). However, there are no significant differences between male and female athletes in terms of who they communicate with the most. The researcher found that knowing the best communication development, style and timing between managers and coaches with athletes and officials in the WIAC can serve as a foundation for DCM principles and recommendations and can help promote the NCAA Division 3 conference.